Estrogen regulates duodenal calcium absorption and improves postmenopausal osteoporosis by the effect of ERβ on PMCA1b - Yingyang Wu; Xian Guo; Airui Jiang; Jianying Bai; Xubiao Nie (Scientific Reports)
Abstract Dietary calcium supplements can prevent osteoporosis, and our previous investigation demonstrated a notable increase in duodenal calcium absorption due to the impact of estrogen. The decrease of estrogen level in postmenopausal women is significantly associated with an increased incidence of osteoporosis. In this study, we further investigated the role of estrogen regulating duodenal calcium absorption in osteoporosis and elucidated its underlying molecular mechanism. We recruited ten young women in the prefollicular stage and ten menopausal women for the study. Furthermore, we performed trials on mice, as well as human duodenal epithelial cells and SCBN cells. The measurement of calcium absorption in the duodenum of mice was conducted through single-pass perfusion in vivo. We used a calcium imaging system to evaluate calcium absorption in SCBN cells. The bone mineral density was measured using small animal computed tomography and a bone densitometer. Furthermore, The expression levels of calcium transport proteins, namely plasma membrane calcium pump (PMCA1b) and transient receptor potential cation channel (TRPV6), were evaluated using western blot analysis. Compared to young women, postmenopausal women exhibited significant reductions in estrogen levels, bone mineral density, and the expression of PMCA1b and TRPV6 in duodenal mucosal tissues (P < 0.05). A positive correlation was also observed between estrogen levels, the expression of PMCA1b and TRPV6, and bone mineral density (P < 0.05). The estrogen levels, the expression of PMCA1b and TRPV6 in the duodenal mucosa, calcium absorptions, and bone mineral density were observed to be decreased in ovariectomized mice based on in vivo animal experiments (P < 0.05). However, estrogen upplementation can enhance duodenal calcium absorptions and ameliorate osteoporosis in ovariectomized mice, with its primary mechanism of action being the regulation of PMCA1b expression and function (P < 0.05). The findings from SCBN cells further confirm that estrogen enhances duodenal calcium absorption through the effect of ERβ on PMCA1b. Estrogen enhances the expression and functionality of PMCA1b in duodenal mucosal cells via ERβ, promoting duodenal calcium absorption and ameliorating postmenopausal osteoporosis.